348 A phase 2 umbrella study of retifanlimab (INCMGA00012) alone or in combination with other therapies in patients with advanced or metastatic endometrial cancer (POD1UM-204, GOG 3038, ENGOT-en12/NOGGO). (9th November 2020) - Slomovitz, Brian; Monk, Bradley; Moxley, Katherine; Ghali, Nadeem; Sokol, Justyna Fronczek; Tian, Chuan; Bourayou, Nawel; Sehouli, Jalid
Abstract : Background: Management of advanced endometrial cancer after failure with platinum therapy remains a challenge. Tumors characterized by DNA repair abnormalities are associated with high numbers of neoantigens; immunotherapy is promising in this setting as demonstrated in studies with checkpoint inhibitors (CPI). 1–6 Overcoming emerging resistance to CPI through novel combinations is a focus of research. Retifanlimab is an investigational humanized immunoglobulin G4 monoclonal antibody against programmed cell death 1 (PD 1). In POD1UM-101, retifanlimab monotherapy demonstrated acceptable tolerability and durable clinical benefit in multiple advanced tumor types, including pretreated endometrial cancer. 7 POD1UM-204 is designed to further investigate efficacy and safety of retifanlimab alone or in combination with other immunotherapy or targeted agents in patients with advanced/metastatic endometrial cancer. Methods: POD1UM-204 is a phase 2, multicenter, nonrandomized, open-label, umbrella study in women =18 years of age, with histologically confirmed diagnosis of advanced/metastatic endometrial cancer that has progressed on or after platinum-based chemotherapy. Patients must have an ECOG performance status =1, at least 1 measurable tumor lesion by Response Evaluation Criteria in Solid Tumors v1.1, and provide tumor tissue at baseline.Approximately 220 patients will be enrolled into 4 treatment groups: Group A–patients with MSI-H (microsatellite instability high) endometrial cancer and no prior CPI therapy (up to 100 patients) receiving retifanlimab monotherapy; Group B–patients with dMMR (deficient DNA mismatch repair) or POLE (DNA polymerase epsilon) endometrial cancer and no prior CPI therapy (up to 40 patients) receiving retifanlimab monotherapy; Group C–patients with unselected endometrial cancer and regardless of prior CPI treatment (up to 40 patients) receiving retifanlimab plus epacadostat (indoleamine 2, 3-dioxygenase inhibitor); and Group D–patients with endometrial cancer and activating fibroblast growth factor receptor (FGFR1, 2 or 3) mutations or alterations outside of the kinase domain and regardless of prior CPI treatment (up to 40 patients) receiving retifanlimab plus pemigatinib (FGFR1, 2, 3 inhibitor) (figure 1). Patients can receive up to 26 treatment cycles if they continue to derive benefit and have not met criteria for withdrawal.The primary study objective is evaluating retifanlimab monotherapy antitumor activity (objective response rate [ORR] determined by independent central review [ICR]) in Group A. Secondary study objectives include assessing additional efficacy measures (duration of response, disease control rate and progression-free survival by ICR, and overall survival) in Group A; determining clinical activity (ORR by the investigator) in Groups B, C and D; and evaluating safety and tolerability of retifanlimab. Results: N/A Conclusions: N/A Acknowledgements: This study is sponsored by Incyte Corporation (Wilmington, DE). Trial Registration: ClinicalTrials. gov Identifier: NCT04463771 ; EudraCT 2020-000496-20 Ethics Approval: The study was approved by institutional review boards or independent ethics committees of participating institutions. Consent: N/A References: Mittica G, Ghisoni E, Giannone G, et al. Checkpoint inhibitors in endometrial cancer: preclinical rationale and clinical activity. Oncotarget 2017;8:90532–544. Di Tucci C, Capone C, Galati G, et al. Immunotherapy in endometrial cancer: new scenarios on the horizon. J Gynecol Oncol 2019;30:e46. Brooks R, Fleming G, Lastra R, et al. Current recommendations and recent progress in endometrial cancer. CA Cancer J Clin 2019;69:258–79. Makker V, Rasco D, Vogelzang N, et al. Lenvatinib plus pembrolizumab in patients with advanced endometrial cancer: an interim analysis of a multicentre, open-label, single-arm, phase 2 trial. Lancet Oncol 2019;20:711–8. Marabelle A, Le D, Ascierto P, et al. Efficacy of Pembrolizumab in patients with noncolorectal high microsatellite instability/mismatch repair–deficient cancer: results from the phase II KEYNOTE-158 study. J Clin Oncol 2020;38:1–10. Oaknin, A, Duska L, Sullivan R, et al. Preliminary safety, efficacy, and pharmacokinetic/pharmacodynamic characterization from GARNET, a phase I/II clinical trial of the anti–PD-1 monoclonal antibody, TSR-042, in patients with recurrent or advanced MSI-h and MSS endometrial cancer. Gynecol Oncol 2019;154(suppl 1):17 [Abstract 33]. Mehnert JM, Joshua AM, Lakhani N, et al. First-in-human phase 1 study of INCMGA00012 in patients with advanced solid tumors: interim results of the cohort expansion phase. J Immunother Cancer 2018;6(suppl 1):115 [Abstract P669].